Sistem Pendeteksi Posisi Kendaraan Kecil pada Dump Truck Tambang menggunakan Modul Radio Frekuensi 433 MHz dan Radar Ultrasonik - Riska Tea Ayu Cindy Mavia; Diky Siswanto Siswanto; Gigih Priyandoko (Teknik Elektro Fakultas Teknik Universitas Widyagama Malang, 2022)
Accidents with mining dump trucks are still common, especially those with small vehicles located in mining locations. The limited visibility of the driver of the large dump truck to see small vehicles around it cause these accidents. This paper presents a small vehicle detection system prototype designed to improve the visibility of the dump truck’s driver. This system works by initially a dump truck detecting the 433 MHz radio frequency, which indicates the small vehicle is around the dump truck. A buzzer sound, controlled by Fuzzy logic according to the distance of small vehicles, also equips the system. It then triggers the truck’s ultrasonic radar to sense the position of small vehicles. The warning information will be displayed on the 16 x 2 LCD. At the same time, a TFT LCD presents the angle and distance of small vehicles. With this system, a dump truck's driver can realize the presence of small vehicles earlier and detect the position and distance of those vehicles.